Interferon‐gamma with peginterferon alpha‐2a and ribavirin in nonresponder patients with chronic hepatitis C (ANRS HC16 GAMMATRI). Issue 2 (22nd January 2013) - Couzigou, Patrice; Pérusat, Sophie; Bourlière, Marc; Trimoulet, Pascale; Poynard, Thierry; Leroy, Vincent; Marcellin, Patrick; Foucher, Juliette; Bronowicki, Jean‐Pierre; Chêne, Geneviève; ,; Oules, V; et al.
Abstract Background and Aim Interferon‐gamma‐1b (IFN‐γ‐1b) improves alpha interferon (IFN‐α) inhibition of hepatitis C virus (HCV) replication in replicon system. We described virological response after addition of IFN‐γ to a combination of ribavirin/peginterferon (PEG‐IFN)‐α‐2a or α‐2b. Methods In this non‐comparative, multicenter trial, patients chronically infected by HCV who were nonresponders to a previous treatment by PEG‐IFN and ribavirin were restarted on a regimen of PEG‐IFN‐α‐2a (180 μg/week) + ribavirin (1000–1200 mg/day) for 16 weeks. If HCV‐RNA decreased less than 2 log10 copies/mL (nonresponders), and if PEG‐IFN‐α‐2a and ribavirin dosages were unchanged while tolerance was good, IFNγ‐1b (100 μg three times per week) was added for the last 32 weeks of treatment. Virological response was evaluated at week 28 (12 weeks after initiation of IFN‐γ‐1b). Results Among the 48 patients started on dual therapy, 23 patients (47%) were nonresponders at week 12 and received IFN‐γ‐1b from week 16 onward. Their mean HCV‐RNA (log10 IU/mL) was 6.83 at baseline, 5.81 at week 12, and 5.63 at week 28. No patient reached undetectable HCV‐RNA at week 28 (upper bound of 95% confidence interval: 14.8%); none had a decrease > 1 log10 IU/mL. One case of grade 4 neutropenia was reported. Conclusion Among the strictly selected nonresponders, IFN‐γ‐1b (at a dosage of 100 μg thrice a week) in combination with PEG‐IFN‐α‐2a and ribavirin failed to show virological efficacy.